10 Deep brain stimulation of the bilateral habenula for treatment resistant depression: preliminary results of six patients. Issue 8 (20th July 2020) - Zhang, Chencheng; Zhang, Yingying; Li, Jun; Li, Dianyou; Jin, Haiyan; Voon, Valerie; Sun, Bomin
Abstract : Objectives/Aims: The habenular nucleus is a set of well-conserved structures involved in aversive reward and is inhibitory to major monoaminergic nuclei. Several cases indicated that it is a promising deep brain stimulation (DBS) target for treatment of major depressive disorder (MDD). In this study, we assess the effectiveness and safeness of bilateral habenula DBS in MDD patients. Methods: Six patients with MDD underwent DBS of bilateral habenula in the study (5 bipolar disorder and 1 unipolar disorder; 4 males and 2 females). Quantitative susceptibility mapping was used to visualize the habenula. Hamilton depression scale (HAM-D) and Montgomery-Asberg Depression Scale (MADRS) were used to qualify the severity of depressive symptoms and were the primary outcome measures. Response to DBS was defined as a 50% decrease on the HAM-D and MADRS compared to baseline. The pittsburgh sleep quality index (PSQI), 36-Item short form survey (SF-36) and sheehan disability scale (SDS) were used to assess quality of sleep, quality of life and disability respectively. These measures were implemented at baseline and 1-month, 3-month, 6-month and 12-month after surgery. Results: At one-month follow-up, compared to the baseline, the HAM-D and MADRS mean scores significantly decreased from 24 (2.2), 31 (4.1) to 14 (7.3), 17.3 (9.8) respectively and four patients were categorized as responders to DBS (p=0.018, p<0.01). Moreover, the PSQI mean score dramatically decreased from 16.3 (2.1) to 9.7 (3.3) (p<0.01) and the SF-36 total mean score increased from 317 (119.4) to 540 (228.3) (p=0.012). The SDS mean score also significantly decreased (p<0.05). There were no permanent side effects observed. Conclusions: The results of one-month follow-up demonstrated that DBS of bilateral habenula may relieve the depressive symptoms rapidly. The quality of sleep, quality of life and functioning also improved.